“RUSSIAN-RUSSIAN” ECONOMY AS THE MECHANISM OF THE INTEGRATION OF RUSSIAN-SPEAKING MIGRANTS IN THE RECEIVING COUNTRIES - Ryazantsev, S.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
Emigration from Russia led to the forcing and expansion of Russian-speaking communities in various countries of the world. The Russian-speaking audience is very large and represents a large segment of some national economies. The example of some countries of the world (the USA, Thailand, Australia, and European countries) explores a new social phenomenon - the “Russian-speaking” economy, which occupies an important place in the life of Russian-speaking communities and includes a system of institutions, infrastructure and economic relations between their representatives, based on the use and dominance of the Russian language. Newly arrived immigrants from Russia and the countries of the former USSR are integrated into host societies, acquiring first experience of work and living in new conditions more often in the “Russian-speaking” economy. Russian-speaking communities are expanding due to a constant supply of immigration from Russia - it is not just new workers, but also buyers of goods and consumers of services. In some cases, the development of a “Russian-speaking” (ethnic) economy combined with other factors is a stimulus for migration from Russia to host countries.